INNOVATION AND ENTREPRENEURSHIP WITHIN HEALTH EDUCATION international. (ROUTLEDGE, 2026)
Recognizing the growing significance of innovation and entrepreneurship in the field of health education, this novel volume discusses digital skills, collaborative learning and contemporary curricular challenges in order to foster innovative and entrepreneurial mindsets.Against the backdrop of an evolving healthcare system characterized by the delivery of consumer-led, data-driven, targeted healthcare solutions, the chapters in the book spotlight entrepreneurship as a vital component of the New Health Economy and the role of education in supporting entrepreneurship and innovation among medical professionals and trainees. Citing international perspectives on curriculum initiatives in various educational settings, the book presents case studies of health entrepreneurship frameworks, startups and the idea of an entrepreneurial healthcare ecosystem that supports networking, professional development and technological advancement.Supporting the use of entrepreneurship strategies for educational purposes within medical education settings, this book will be of interest to scholars, researchers, faculty and postgraduate students in the fields of health education, curriculum studies, technology in education, medical education and entrepreneurship.
Keywords: Health education -- Technological innovations.; Entrepreneurship.; Medical education -- Curricula.; Interdisciplinary approach in education.; elektronické knihy; electronic books